Adsorptive removal of gaseous formaldehyde at realistic concentrations. Issue 4 (August 2020) - Lara-Ibeas, Irene; Megías-Sayago, Cristina; Louis, Benoît; Le Calvé, Stéphane
Highlights: Formaldehyde adsorption was studied over carbon, MOF, silica and zeolites at ppb levels. HKUST-1 showed the highest formaldehyde affinity. Formaldehyde adsorption is strongly related to Al content in ZSM-5 zeolites. Abstract: Due to analytical reasons, adsorption capacity is often determined at very high concentrations which is not representative of a real environment. The aim of this work is to provide experimental data of formaldehyde adsorption capacity at realistic levels (∼164 ppb) thanks to a near real-time powerful formaldehyde analyser recently developed in our laboratory. Gaseous formaldehyde breakthrough experiments were conducted on a broad spectrum of materials including carbon, zeolites, metal organic framework and mesoporous silica in order to determine their adsorption capacity. Among these materials, HKUST-1 exhibited the highest adsorption capacity (504 μg/g ads) followed by MgZSM-5 (35 μg /g ads), SBA-16 (29 μg/g ads), ZSM-5 (10–26 μg/g ads) and Carbopack® B (4 μg/g ads). In the case of ZSM-5 zeolites, the results revealed that formaldehyde adsorption was related to their aluminium content. The presence of aluminium implies more bridging hydroxyl groups Si-(OH)-Al that act as Brønsted acid sites interacting with formaldehyde molecules. Despite the moderate adsorption capacity of ZSM-5 zeolites, they can be considered as promising candidates for gas analysis applications, for example where a good analytical blank is essential for accurate measurements.